The Concept of Money According to the Thought of Ibn Taymiyah and Imam Ghazali and its Implementation in the Economic Field - Firdaus, Muhammad Irkham; Pradhana, Theo Aditya; Nasution, Saiful (AL- IKTISAB Journal of Islamic Economic Law, 2020)
The current concept of paper money has a negative impact on people's lives. Many Muslim leaders formulated the concept of money that is more like and not harmful, including Ibn Taymiyah and Imam Ghazali. He has scientific works that discuss the concept of money. So in this paper will discuss the concepts of paper money according to Ibn Taymiyah and Imam Ghazali. This research used library method. The results, comparison of Ibn Taymiyah and Imam Ghazali’s thought regarding a good and right money system, which is in accordance with Islamic principles and benefits all parties is as follows, money as a medium of exchange, money has no utility function, money is not a commodity, money as a measure of the value of goods, money must have a fixed value, and money must flow and circulate not to be hoarded.